Studies on the Preparation of Fish Protein Concentrate - ISMAIL, P. K.; MADHAVAN, P.; PILLAI, V. K. (Fishery Technology, 1968)
The paper deals with the method of preparation of an edible fish protein concentrate from cheap miscellaneous fish. The method consists in cooking the fish with 0.5% glacial acetic acid, and extracting batchâ€”wise, using ethyl alcohol followed by an azeotropic mixture of hexane and alcohol (B. Pt. 58 68Â°C). The product is finally vacuum dried during which the residual solvent is also removed. The concentrate prepared by this method contains 85% protein of which 96% is pepsin digestible. The product is practically odourless and almost white in colour.